Determinação da constante de afinidade e cinética da interação lectina ArtinM-célula leucêmica (NB4) por meio de técnicas piezoelétrica e eletroquímica - Martins, Denise Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
ArtinM, a D-mannose-binding lectin from Artocarpus heterophyllus (jackfruit), interacts with N-glycans on cell surface receptors triggering cell migration, degranulation, and cytokine release. Because malignant transformation is often associated with altered expression of cell surface glycans, this work evaluated the interaction of ArtinM with human myelocytic leukemia cells, such as acute promyelocytic leukemia, NB4, by piezoelectric techniques of the Quartz Crystal Microbalance (QCM) and by electrochemical techniques of Electrochemical Impedance Spectroscopy (EIS). It was developed, for both techniques, a surface recognition capable of performing the biological interaction between lectin-cell and transducte them in electric signal. The surface was formed by immobilization of ArtinM in Au metal surfaces by over a self-organized monolayer constructed by a mixture of two alkanothiols, 11-mercaptoundecanoic acid (11-MUA) as an anchor, and 6-mercaptoethanol (6- MetOH) as a spacer. Concentrations of NB4 cells, previously fixed with paraformaldeide, were left in contact with the immobilized lectin on electrode. After the interaction measurements evaluated by QCM and EIS, and applying the model of Langmuir isotherm, it was possible to obtained both kinetic and affinity constants. Using QCM, beyond the apparent affinity constant, was possible to extract kinetic parameters Ka (association kinetic constant) = (1.8 ± 1.1) 10-7 cel mL-1, kon (association constant) = (3.6 ± 1.0) x10- 10 mL cel- 1 s- 1 and koff (dissociation constant) = (20.3 ± 6.6) x10- 4 s- 1 . The value of the apparent affinity constant (K') was (4.4 ± 0.1) x10- 7 cel mL- 1 by QCM and (9.9 ± 0.2) x10- 5 mL cel- 1 by EIS, the difference between the values comparing both techniques may be related to different factors such as the use of successive addition of NB4 in EIS comparing the in unitary addition in QCM analysis, variation in surface engineering and distinct saturation range.

A lectina vegetal ArtinM, ligante de D-manose, está presente nas sementes da jaca, Artocarpus heterophyllus e possui uma estrutura homotetramérica formada pela associação não covalente de subunidades, sendo que cada subunidade representa um CRD (Carbohydrate Recognition Domain). Por interagir com N-glicanas presente em células de mamíferos, a ArtinM desencadeia diversos processos biológicos, dentre eles a resposta citotóxica sobre células leucêmicas, em especial células NB4 da leucemia promielocitica aguda. Neste trabalho foi estudada a interação ArtinM-NB4 por técnicas piezoeletricas de Microbalança a Cristal de Quartzo (QCM) e eletroquímicas por Espectroscopia de Impedância Eletroquímica (EIS), para tanto foi desenvolvida uma superfície de reconhecimento capaz de realizar a transdução do evento biológico de interação lectina-carboidrato em elétrico. A superfície de reconhecimento foi formada pela imobilização da lectina ArtinM em superfícies metálicas de Au por meio de uma monocamada auto-organizada, utilizando uma mistura de dois alcanotióis, o ácido 11-mercaptoundecanóico (11-MUA), como ancora, e o 6-mercaptoetanol (6-MetOH), como espaçador. As várias concentrações de células NB4 previamente fixadas foram deixadas em contato com a lectina imobilizada no eletrodo para que ocorressem as interações desejadas. Após as medidas terem sido avaliadas utilizando-se QCM e EIS, e aplicando o modelo da isoterma de Langmuir, foi possível determinar as constantes cinéticas e de afinidade. Nas medidas obtidas utilizando a QCM, para além da constante de afinidade aparente, foi possível extrair os parâmetros cinéticos: Ka (constante de associação cinética) = (1,8±1,1)x10-7 mL cel-1, kon (constante de velocidade de associação) = (3,6±1,0)x10-10 mL cel-1s-1 e koff (constante de dissociação) = (20,3±6,6)x10-4 s-1. O valor da constante de afinidade aparente (K') foi de (4,4±0,1)x10-7 mL cel-1 utilizando...
Keywords: Biotecnologia; Lectinas; Leucemia; Leukemia